The Tale of Two Newspapers: Perceptions and Representations of Iranian International Relations Discourse - Nazari, Ahmad (The Indonesian Journal of Social Studies, 2019)
One of the research topics which intrigues researchers in the subject areas of applied linguistics, international relations and politics is political discourse and the way it is perceived and represented in the media. Researchers have analysed and interpreted the political and international relations discourse of various politicians and diplomats in different countries. By the same token, Iran, as a country with an influence on the political issues of the Middle East and a role in international dynamics and trends, has devoted a plethora of research to itself where researchers have examined and critiqued the international and foreign policies of Iran in various periods of time, in relation to various countries and in connection with various political and international events and situations. However, a search carried out by the present researcher showed that there are not many publications on how the British mass media, newspapers in particular, perceive and represent the Iranian governmentâ€™s international relations discourse. To address this lacuna, a corpus of news stories and reports extracted from two renowned British newspapers, the Guardian and Daily Mail, was analysed by adopting a double hermeneutic content analysis approach. The results suggest that the two newspapers, in spite of being famous for having polar political views, seem to have similar perceptions and representations of the above discourse. The study also provides directions for further research in other contexts.Â